Optimizing the Use of History Textbook through Brain-Based Learning (Paramita: Historical Studies Journal, 2019)
This research was conducted based on the researchers' assumption to low optimal use of history textbook in school. Such ineffective condition was indicated from functioning book only as a resource material for examination. Even, the existence of the book tends to be a burden either for the teachers and the students. Therefore, brain-based learning can be an alternative to optimize the textbook to improve students’ historical thinking and understanding. To achieve this goal, inquiry naturalistic model proposed by Licoln and Guba (1985) was employed in history learning in one SMA in Bandung. Data were collected through observing, tracing and witnessing to historical learning by implementing brain-based learning approach carried out in the classroom. The analysis results revealed that this model brings several impacts, namely: (1) Students are not familiar to express their emotions during their history learning. However, applying cognitive and emotion aspects of the students may help them remember historical facts more easily, (2) the use of cognitive and emotional learning system also facilitates the students to improve their ability in identifying and classifying the facts from the textbook, (3) students still find difficulties in associating one fact to the others, and (4) generally, this model affects students’ historical understanding which is indicated from their ability to comprehend the history subject well, to obtain valuable life values, to figure out historical figures, social conflicts, and to understand social changes in the society. Penelitian ini dilakukan berdasarkan asumsi peneliti terhadap rendahnya penggunaan optimal buku teks sejarah di sekolah. Bahkan, keberadaan buku cenderung menjadi beban baik bagi guru maupun siswa. Oleh karena itu, brain-based learning  dapat menjadi alternatif untuk mengoptimalkan buku teks untuk meningkatkan pemikiran dan pemahaman historis siswa. Untuk mencapai tujuan ini, model naturalistik inkuiri yang diajukan oleh Licoln dan Guba (1985) digunakan dalam pembelajaran sejarah di satu SMA di Bandung. Data dikumpulkan melalui pengamatan, penelusuran, dan saksikan pembelajaran sejarah dengan menerapkan pendekatan brain-based learning yang dilakukan di kelas. Hasil analisis mengungkapkan bahwa model ini membawa beberapa dampak, yaitu: (1) Siswa tidak terbiasa mengekspresikan emosi mereka selama pembelajaran sejarah mereka. Namun, menerapkan aspek kognitif dan emosi siswa dapat membantu mereka mengingat fakta sejarah lebih mudah, (2) penggunaan sistem pembelajaran kognitif dan emosional juga memfasilitasi siswa untuk meningkatkan kemampuan mereka dalam mengidentifikasi dan mengklasifikasikan fakta dari buku teks, (3) siswa masih menemukan kesulitan dalam mengaitkan satu fakta dengan yang lain, dan (4) umumnya, model ini mempengaruhi pemahaman historis siswa yang ditunjukkan dari kemampuan mereka untuk memahami subjek sejarah dengan baik, untuk mendapatkan nilai-nilai kehidupan yang berharga, untuk mencari tahu tokoh-tokoh sejarah , konflik sosial, dan untuk memahami perubahan sosial di masyarakat.